Rancang Bangun Sistem Informasi Terpadu Salon Rumah Cantik Nadia Berbasis Macro Microsoft Excel - Ibrahim Musa; Sekta Lonir Oscarini; Fara Yaska (Jurnal EKSIS, 2023)
Abstract : This study aims to design and build an integrated or computerized information technology system, making it easier for salon employees to enter data, search data, and make monthly and annual reports, thereby reducing errors that occurred before. The type of data used in this study uses qualitative and quantitative research data types using primary and secondary data sources. The data collection techniques used were observation, interviews, documentation, and literature study. This study used data flow diagrams system modeling and entity relationship diagrams. The analysis tool used was macros in microsoft excel, which can facilitate data processing properly. The result of this study was the application of an integrated information system that was more effective and more efficient than the system previously applied to Rumah Cantik Nadia Salon.